Investigating Maar Formation and the climate history of Southern Argentina–the Potrok Aike Maar Lake Sediment Archive Drilling Project (PASADO) - Zolitschka, Bernd; Corbella, Hugo; Maidana, Nora Irene; Ohlendorf, Christian (Scientific Drilling)
Evidence is increasing that the Southern Ocean plays a key role in the global climate system. The southern hemisphere contains more than 90% of the world’s ice, and eighty-one percent of its total surface area is covered by oceans. On global terms, the most extreme oceanic character is encountered between 40°S and 60°S latitude, where land (Patagonia and a few islands) comprises only 2% of the surface area. Terrestrial archives of past climate changes are thus extremely scarce at these latitudes. As Patagonia is subject to shifts in polar and mid-latitude winds, pressure fi elds, and precipitation regimes, as well as to variations related to the El Niño Southern Oscillation (ENSO) and the Antarctic Oscillation (AO), it has the unique potential to record variations in the hydrological cycle, changes in aeolian dust deposition, the frequency of volcanic activity, and other natural forces that control climatic conditions. Lake sediments can provide important archives for such terrestrial climatic and environmental reconstructions. In the semi-arid steppe region of Patagonia, however, most of the lakes are periodically dry or ephemeral. One exception is the 100-m-deep crater lake Laguna Potrok Aike (Fig. 1), a 770 ± 220 thousand year old maar situated in the province of Santa Cruz, Argentina. The lake is located in the Pali Aike Volcanic Field (Fig. 2), the southernmost back-arc Neozoic volcanic fi eld of South America. As Laguna Potrok Aike has not been reached by any Pleistocene ice advance during the last 1 Ma, it is potentially the only mid-latitude lake in the Southern Hemisphere with a continuous sedimentary record covering several glacial to interglacial cycles. In addition to global reconstructions, regional climatic variations represent other important aspects of research. Fil: Zolitschka, Bernd. Universitat Bremen; Alemania Fil: Corbella, Hugo. Universidad Nacional de la Patagonia Austral; Argentina Fil: Maidana, Nora Irene. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. ...